Answer: The verification is done below.
Step-by-step explanation: We are given to show that the function
is a solution to the following differential equation :
![t^2y^(\prime\prime)-ty^\prime+y=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2020/formulas/mathematics/college/sdws7wkv3xzxghnusbx5zk2c21pxwmpl4s.png)
If
we have
![y^\prime=(d)/(dt)f(t)=(d)/(dt)(2t+5t\ln t)=2*1+5\ln t+5t*(1)/(t)\\\\\\\Rightarrow y^(\prime)=7+5\ln t,\\\\\\y^(\prime\prime)=(d)/(dt)(7+5\ln t)=0+5*(1)/(t)=(5)/(t).](https://img.qammunity.org/2020/formulas/mathematics/college/sxoakcw1z6nc7522bbzw9yx5oxhllboc82.png)
Therefore, we get
![L.H.S.\\\\=t^2y^(\prime\prime)-ty^\prime+y\\\\=t^2*(5)/(t)-t(7+5\ln t)+(2t+5t \ln t)\\\\\\=5t-7t-5t\ln t+2t+5t\ln t\\\\=0\\\\=R.H.S.](https://img.qammunity.org/2020/formulas/mathematics/college/l6d97qqhibl10btrnjog02hwrl873fgyms.png)
Thus, the function
is a solution to the given differential equation.
Hence showed.